Training of catching teams and reduction of back scratches in broilers - Pilecco,M (2013)
This study evaluated the efficacy of training of catching teams and reduction of back scratches in broilers. The study was carried out in a large broiler company between January and October of 2010, in the region of Dourados, Brazil. During that period, 80 samplings were performed in 80 broiler houses in the micro-regions covered by the company. When broilers were 43 days old, when 5% of the birds in each house were evaluated immediately after catching, when birds were already inside the plastic crates, ready to be transported to the processing plant. Out of a total number of 1,177,600 total, 58,880 broilers were evaluated. Four catching teams (A, B, C, and D), with 24 people each, were trained for four consecutive weeks. By the end of the training course, it was observed that average age of the team members and time of catching affected the incidence of back scratches. Training had a positive effect, reducing in 33.13% the incidence if back scratches caused by the catching team due to incorrect catching procedures. Therefore, continuous training is required, particularly when the catching teams are composed of young and inexperienced workers.